2018
DOI: 10.5114/kitp.2018.76481
|View full text |Cite
|
Sign up to set email alerts
|

Applications of low-cost 3D printing in left atrial appendage closure using epicardial approaches – initial clinical experience

Abstract: IntroductionLeft atrial appendage occlusion procedure (LAAO) became an alternative method for stroke prevention in atrial fibrillation (AF) patients with contraindication or intolerance for oral anticoagulation therapy. However, LAA anatomy is complex with several different types of LAA morphology. Therefore matching the correct size of a delivery device to LAA morphology is difficult. In such circumstances, the 3D-printed model of LAA closure may be useful for preoperative planning which increases the efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…However, there is a large group of patients in whom OAC therapy is contraindicated or ineffective [1,17] or in whom OAC present fatal complications observed that are observed also in new oral anticoagulants[18]. In recent years LAAC has become an increasingly popular alternative [1921]. ESC guidelines now include LAAC as a Class 2 B recommendation for patients with AF with a contraindication to OAC or a clinical history of severe bleeding [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a large group of patients in whom OAC therapy is contraindicated or ineffective [1,17] or in whom OAC present fatal complications observed that are observed also in new oral anticoagulants[18]. In recent years LAAC has become an increasingly popular alternative [1921]. ESC guidelines now include LAAC as a Class 2 B recommendation for patients with AF with a contraindication to OAC or a clinical history of severe bleeding [1].…”
Section: Discussionmentioning
confidence: 99%
“…8 procedures are currently one of the fastest developing branches of interventional cardiology and indications for LAAO are extending. 1,4,9,10 Previous short-term studies showed that LAAO procedures are efficacious, safe and are widely performed in clinical practice. 11 However, few published studies evaluate the long-term efficacy of LAAO procedures in high risk patients based on CHA 2 DS 2 -VAS-score.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years left atrial appendage occlusion (LAOO) has become an alternative treatment for stroke prevention in AF patients regardless of patients age . LAAO procedures are currently one of the fastest developing branches of interventional cardiology and indications for LAAO are extending . Previous short‐term studies showed that LAAO procedures are efficacious, safe and are widely performed in clinical practice .…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between the measured values of each method and the size of occlude are also not clear. Previous results suggested that the LAA ostial size measured by CTA was larger than that of TEE and DSA [10,11]. Reports by Chow et al indicated that the narrowest limits of agreement were shown in the correlation of the device size and CTA measurements, the choice of the left atrial appendage occluder size based on the CTA measurements was more accurate than the conventional TEE [12].…”
Section: Discussionmentioning
confidence: 93%